Treatment of Renal Artery Stenosis in a Solitary Kidney Using Cutting Balloon Angioplasty in a Paediatric Patient. Issue 12 (February 2019) - Hall, Thomas C; Williams, Alun; Hussain, Farida; O'Neill, Richard
Aims: Renovascular hypertension is a rare cause of paediatric hypertension. It is however, a potentially treatable cause particularly when caused by renal artery stenosis (RAS). Materials and Methods: We present the case of an 11-month-old girl presenting with cardiac dysfunction. She was found to be hypertensive with a systolic blood pressure >180mmHg. DMSA demonstrated a small right kidney and a divided renal function of 6% on the right and 94% on the left. Spectral analysis demonstrated abnormal waveforms suggestive of RAS of the left kidney. Results: Angioplasty with a cutting balloon was successful. Blood pressure measurements, renal function and left ventricular function improved. Conclusion: RAS can be successfully treated with cutting balloon angioplasty after failure of convention balloon angioplasty to relieve the narrowing. In our case, there was an immediate successful angiographic result that on mid-term follow-up demonstrated significant improvement in clinical and biochemical outcomes and cessation of all anti-hypertensive medication.